Incidence and prognosis of ventilator-associated tracheobronchitis (TAVeM): a multicentre, prospective, observational study. Issue 11 (November 2015) - Martin-Loeches, Ignacio; Povoa, Pedro; Rodríguez, Alejandro; Curcio, Daniel; Suarez, David; Mira, Jean-Paul; Cordero, Maria Lourdes; Lepecq, Raphaël; Girault, Christophe; Candeias, Carlos; Seguin, Philippe; Paulino, Carolina; et al.
Summary: Background: Ventilator-associated tracheobronchitis has been suggested as an intermediate process between tracheobronchial colonisation and ventilator-associated pneumonia in patients receiving mechanical ventilation. We aimed to establish the incidence and effect of ventilator-associated tracheobronchitis in a large, international patient cohort. Methods: We did a multicentre, prospective, observational study in 114 intensive care units (ICU) in Spain, France, Portugal, Brazil, Argentina, Ecuador, Bolivia, and Colombia over a preplanned time of 10 months. All patients older than 18 years admitted to an ICU who received invasive mechanical ventilation for more than 48 h were eligible. We prospectively obtained data for incidence of ventilator-associated lower respiratory tract infections, defined as ventilator-associated tracheobronchitis or ventilator-associated pneumonia. We grouped patients according to the presence or absence of such infections, and obtained data for the effect of appropriate antibiotics on progression of tracheobronchitis to pneumonia. Patients were followed up until death or discharge from hospital. To account for centre effects with a binary outcome, we fitted a generalised estimating equation model with a logit link, exchangeable correlation structure, and non-robust standard errors. This trial is registered with ClinicalTrials.gov, number NCT01791530 . Findings: Between Sept 1, 2013, and July 31, 2014, we obtained data for 2960 eligible patients, of whom 689 (23%) developed ventilator-associated lower respiratory tract infections. The incidence of ventilator-associated tracheobronchitis and that of ventilator-associated pneumonia at baseline were similar (320 [11%; 10·2 of 1000 mechanically ventilated days] vs 369 [12%; 8·8 of 1000 mechanically ventilated days], p=0·48). Of the 320 patients with tracheobronchitis, 250 received appropriate antibiotic treatment and 70 received inappropriate antibiotics. 39 patients with tracheobronchitis progressed to pneumonia; however, the use of appropriate antibiotic therapy for tracheobronchitis was associated with significantly lower progression to pneumonia than was inappropriate treatment (19 [8%] of 250 vs 20 [29%] of 70, p<0·0001; crude odds ratio 0·21 [95% CI 0·11–0·41]). Significantly more patients with ventilator-associated pneumonia died (146 [40%] of 369) than those with tracheobronchitis (93 [29%] of 320) or absence of ventilator-associated lower respiratory tract infections (673 [30%] of 2271, p<0·0001). Median time to discharge from the ICU for survivors was significantly longer in the tracheobronchitis (21 days [IQR 15–34]) and pneumonia (22 [13–36]) groups than in the group with no ventilator-associated lower respiratory tract infections (12 [8–20]; hazard ratio 1·65 [95% CI 1·38–1·97], p<0·0001). Interpretation: This large database study emphasises that ventilator-associated tracheobronchitis is a major health problem worldwide, associated with high resources consumption in all countries. Our findings also show improved outcomes with use of appropriate antibiotic treatment for both ventilator-associated tracheobronchitis and ventilator-associated pneumonia, underlining the importance of treating both infections, since inappropriate treatment of tracheobronchitis was associated with a higher risk of progression to pneumonia. Funding: None.